PENGARUH ETIKA, KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP SKEPTISISME PROFESIONAL AUDITOR PADA PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN PROVINSI SUMATERA SELATAN - Intan Permatasari; Kartika Rachma Sari; Indra Satriawan (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This study aims to determine the effect of Ethics, Competence and Auditor Independence on Professional Skepticism of Auditors. This study used a quantitative method using primary data obtained by directly distributing the tested questionnaires. The population in this study were auditors at the BPKP Representative for South Sumatra Province. The sampling technique uses a purposive sampling technique with the criteria of an auditor having at least one year's work experience and participating in the implementation of the auditing process. The analysis model of this research is Multiple Linear Analysis with data analysis techniques using the SPSS version 25 program. The results of this study can be concluded that ethics has a significant positive effect on auditor professional skepticism, competence has no effect on auditor professional skepticism, independence has a significant positive effect on skepticism auditor professionalism and ethics, competence and auditor independence simultaneously have a significant positive effect on auditor professional skepticism